Kajian Struktural terhadap Novel Bumi Manusia karya Pramoedya Ananta Toer sebagai Referensi Pembelajaran Sastra di Madrasah Aliyah - Indah Permata Sari; Ali Ali; Amaluddin Amaluddin (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2026)
This study examines the structural elements of Bumi Manusia by Pramoedya Ananta Toer as a reference for literature instruction in Madrasah Aliyah. The research is grounded in the need to strengthen students’ critical and contextual understanding of Indonesian literary heritage within secondary Islamic education, where canonical works are often underutilized as analytical teaching materials. The study addresses the following question: how can a structural analysis of the novel—focusing on plot, characterization, setting, theme, and point of view—contribute to effective literature learning in Madrasah Aliyah? Employing a qualitative descriptive method with a structuralist approach, the data were derived from close textual analysis of the novel and relevant pedagogical literature. The findings indicate that the novel presents a coherent narrative structure, complex character construction, and a historically grounded setting that enables students to engage with themes of colonialism, identity, and social justice. The structural elements are interconnected and pedagogically adaptable to competency-based learning objectives in secondary education. The study argues that Bumi Manusia offers not only literary richness but also substantial educational value, making it a relevant and effective reference for developing analytical and reflective literary competence among Madrasah Aliyah students.